Innovative Agrifood Supply Chain in the Post-COVID 19 Era - Skalkos, Dimitris (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The world is changing rapidly in the age beyond Coronavirus. The current period of deprivation and anxiety, together with the coming global economic crisis, will usher in new consumer attitudes and behaviors that will change the nature of today's capitalism. There are signs today of a growing anti-consuming movement with five types of anti-consumerists: life simplifiers, degrowth activists, climate activists, food choosers, and conservation activists. Citizens will reexamine what they eat, how much they eat, and how all this is influenced by class issues and inequality. Consequently, the food supply chain network will have to change dramatically, adjusting to the new attitudes, perceptions and preferences of the consumers of a post-COVID-19 era. Innovation will play a vital role in modernizing the food supply chain to meet the new challenges of the upcoming global economy. The process "from farm to fork" as the holistic approach to the production and consumption of food will become a key factor for the sustainability and the progress of the food industry. This Special Issue is focused on 11 selected topics from different parts of the agrifood supply chain in view of the post-COVID-19 era expanding from innovative scientific insights and technological advances of natural resources, organic pollutants identification, new food product development, traceability, and packaging, chain management, to consumer's attitudes, and eating motivations, aiming to tackle the foreseen changes of global economy.